PENGARUH PROFITABILITAS TERHADAP AUDIT DELAY PADA PERUSAHAAN TERDAFTAR DI BURSA EFEK INDONESIA TAHUN 2022 - Sania, Ratih; Miftah, Achmad Zaki; Rachman, Fatwa Rubiar (Jurnal Nusa Akuntansi, 2024)
Financial reports are one piece of information that plays an important role in the investment business in the capital market. This reflects the importance of timeliness in presenting financial reports to the public. Various obstacles that affect punctuality can come from internal or external to the company. This research aims to determine the effect of profitability on audit delay in companies listed on the Indonesia Stock Exchange in 2022. This research uses secondary data which can be accessed via the Indonesia Stock Exchange in the form of financial reports and annual reports company. The data analysis techniques used are descriptive statistical analysis, classical assumption test, t test, and simple regression analysis using SPSS software. The population of this study consisted of 143 companies that were late in submitting their 2022 financial reports. The sampling method was carried out using a purposive sampling method so that a sample of 91 companies was obtained. The research results show that profitability has an effect on audit delay.